علاقة بعض القدرات الحركية الخاصة بدقة اداء المهارات الاساسية في التنس - عباس, عمار جبار; سامي, شيماء (Sulaimani Journal for Humanities, 2018)
Provided the world has seen in the sports field developed rapidly and effectively in recent years has been this development showed frequent changes in the majority of games including tennis and gained a greater share of these developments, both in the rules of the game or in raising the level of the players capabilities physical and skill and tactical, psychological and mental which was the outcome of sporting achievements achieve high for all levels. In order to be able to keep up winning the game in progress, the researcher focused on the important aspect in which a kinetic capabilities because it is a necessary requirement for the success of the technically gifted side The speed of the ball and an area of the pitch and the diversity of defensive and offensive skills and excellence in performance repetitive game. All this has made the player needs to be rapid control his movements by standing and then return to the movements again and change direction and make the force disparate parts, fast, accurate and meet the sudden and other basic capabilities along with the skill positions, no player's performance can unless it is characterized by a high ability to performance and time appropriate and good accuracy and agility sufficient to perform the skill more than once, and also the Defender of the protection allocated to the region can not unless it is characterized by rapid kinetic transition speed and leg strength to respond, as well as the player to continue playing in the game can not retaining his drive unless it is characterized by private Balthml Based on the مجلة )زانکۆی سلێمانی( القسم )B )للدراسات االنسانیة – العدد )65( عدد خاص لمؤتمر الدولي األول لكلیة التربیة الرياضية 1701 above, the importance of the research is to identify the relationship between some of the kinetic capabilities and basic skills in tennis delight and which are captured by the tests and measurements of its own which enables the trainers to know the weaknesses of the player points thus processed elevate the better. The research problem is the game of tennis sports that require a high level of physical abilities And skills of the beta performance art is acceptable for this is the mutual relationship between the evolution of the physical side of the task and basic skills aspect of the performance of the players when performing the duties assigned to them and as the game of tennis games that vary in intensity and effort an activity characterized intersection rotation rapid jogging with a change of direction and took breaks short as the beginnings of a quick consensus and require the performance of most of the skills and the flexibility to ensure range of motion Asking him if tennis player relies on training to develop components or fitness required elements of the performance, however, the fitness that develop as a result of playing is not considered sufficient for the player that plays the best level for the performance of skill, therefore, all that requires support of the capabilities of the kinetic and evolution along with other skills and abilities so it was necessary for us and through the requirements of the research to know what the relationship between basic skills In a game of tennis and some motor abilities and for the purpose of guiding people interested in this game to focus on the development of these capabilities, which will inevitably lead to the development of the level of performance being one of the basic pillars that support reliable access to complete better. The objectives of the research The research aims to identify the most important motor abilities and basic skills of tennis players. And to identify the relationship between some of the motor capacity and accuracy performance of some of the basic skills of tennis players .oama hypotheses researchers assumed that there is significant correlation Differences between some of the kinetic capabilities with each other, and there is a correlation statistically significant differences between some of the kinetic capabilities and precision of the performance of some of the basic skills of players of tennis, fields of research .. the human sphere: A group of students from the third stage of the academic year (2014-2015). Temporal sphere: for the period from 28/12/2014 until 24/3/2015 spatial area: Tennis foreign courts in the Faculty of Physical Education - University of Diyala.